Problems, prospects and possibilities of inclusive education for physically disabled children in Bangladesh - Md. Abdullah Al Zubayer (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2011